Total oxidation of methane over Pd/Al2O3 at pressures from 1 to 10 atm. Issue 16 (17th July 2020) - Florén, Carl-Robert; Demirci, Cansunur; Carlsson, Per-Anders; Creaser, Derek; Skoglundh, Magnus
Abstract : The kinetics of total methane oxidation over a 0.15 wt% Pd/Al2 O3 monolith catalyst has been measured during temperature programmed methane oxidation experiments at total pressures from 1 to 10 atm and compared with multiscale simulations. Abstract : The kinetics of total methane oxidation over a 0.15 wt% Pd/Al2 O3 monolith catalyst has been measured during temperature programmed methane oxidation experiments at total pressures from 1 to 10 atm and compared with multiscale simulations. The methane conversion can be significantly enhanced by increasing the total pressure at temperatures above 350 °C, which is thanks to a longer residence time that dominates over decreased bulk gas diffusion rates and product inhibition. For the present catalyst, the external mass transfer impacts the methane conversion above 4 atm. With increasing total pressure, the observed methane reactions order decreases at 350 °C whereas it increases at 450 °C due to a more pronounced product inhibition at the lower temperatures. This is also reflected in the apparent activation energy, which increases with increasing total pressure. The multiscale simulations capture the general trends of the experimental results but overestimate the methane conversion at higher temperatures and total pressures. The overestimated activity indicates of an overestimated number of active sites and/or an underestimated external mass transfer resistance.